2021
DOI: 10.4240/wjgs.v13.i7.655
|View full text |Cite
|
Sign up to set email alerts
|

Management of early rectal cancer; current surgical options and future direction

Abstract: Rectal cancer is the second commonest cause of cancer death within the United Kingdom. Utilization of national screening programmes have resulted in a greater proportion of patients presenting with early-stage disease. The technique of transanal endoscopic microsurgery was first described in 1984 following which further options for local excision have emerged with transanal endoscopic operation and, more recently, transanal minimally invasive surgery. Owing to the risks of local recurrence, the current role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…High ligation of IMA in colorectal cancer operation is a simple method that can clean the lymph nodes completely. However, the incidence of intestinal fistula increased significantly, and the postoperative recovery was slow[ 16 ]. In this study, with the investigation of the prognostic impact of the ligation site of IMA in colorectal cancer surgery in 194 patients, it is found that complete mesenteric resection and IMA root LND while preserving the LCA is a more reliable and safe surgical approach in patients undergoing colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…High ligation of IMA in colorectal cancer operation is a simple method that can clean the lymph nodes completely. However, the incidence of intestinal fistula increased significantly, and the postoperative recovery was slow[ 16 ]. In this study, with the investigation of the prognostic impact of the ligation site of IMA in colorectal cancer surgery in 194 patients, it is found that complete mesenteric resection and IMA root LND while preserving the LCA is a more reliable and safe surgical approach in patients undergoing colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In order to apply these treatment strategies in a patient-specific manner, it is important to establish sophisticated indications that can maximize the therapeutic effect. ERC has heterogeneous pathological features, including aggressive behavior and occult lymph node metastasis, with different responses to CRT [11]. Therefore, predicting the risk of lymph node metastasis and local recurrence based on the pathological characteristics of ERC is important to determine the optimal treatment strategy for each patient.…”
Section: Introductionmentioning
confidence: 99%